Central 22q11.2 deletions. Issue 11 (14th August 2014) - Rump, Patrick; de Leeuw, Nicole; van Essen, Anthonie J.; Verschuuren‐Bemelmans, Corien C.; Veenstra‐Knol, Hermine E.; Swinkels, Mariëlle E.M.; Oostdijk, Wilma; Ruivenkamp, Claudia; Reardon, Willie; de Munnik, Sonja; Ruiter, Mariken; Frumkin, Ayala; et al.
<x xml:space="preserve">Abstract</x> 22q11.2 deletion syndrome is one of the most common microdeletion syndromes. Most patients have a deletion resulting from a recombination of low copy repeat blocks LCR22‐A and LCR22‐D. Loss of the TBX1 gene is considered the most important cause of the phenotype. A limited number of patients with smaller, overlapping deletions distal to the TBX1 locus have been described in the literature. In these patients, the CRKL gene is deleted. Haploinsufficiency of this gene has also been implicated in the pathogenesis of 22q11.2 deletion syndrome. To distinguish these deletions (comprising the LCR22‐B to LCR22‐D region) from the more distal 22q11.2 deletions (located beyond LCR22‐D), we propose the term "central 22q11.2 deletions". In the present study we report on 27 new patients with such a deletion. Together with information on previously published cases, we review the clinical findings of 52 patients. The prevalence of congenital heart anomalies and the frequency of de novo deletions in patients with a central deletion are substantially lower than in patients with a common or distal 22q11.2 deletion. Renal and urinary tract malformations, developmental delays, cognitive impairments and behavioral problems seem to be equally frequent as in patients with a common deletion. None of the patients had a cleft palate. Patients with a deletion that also encompassed the MAPK1 gene, located just distal to LCR22‐D, have a different and more severe phenotype, characterized by a higher prevalence of congenital heart anomalies, growth restriction and microcephaly. Our results further elucidate genotype‐phenotype correlations in 22q11.2 deletion syndrome spectrum. © 2014 Wiley Periodicals, Inc.